User interests-based microblog tracing algorithm - YANG Xiao, CHEN Xiuzhen, MA Jin, LIANG Haozhe, LI Shenghong (网络与信息安全学报, 2020)
Microblog information tracing refers to finding the source set of microblog topics according to the analysis of crawled microblog texts and it’s of great significance in the aspect of public opinion control and information security. A user interests-based tracing method (ITM) was proposed. The proposed method calculates the influence of the blogger based on the interest of the microblog blogger, and also calculates the influence of the commentators based on the interest of the commentators. The ranking algorithm was used to score the blogs according to publication time, notability and influence, and the source of the blogs was traced according to the blog score rank. Experimental results show that the accuracy of the proposed algorithm improved about 21% compared with the traditional tracing algorithms.